PENGARUH PENDIDIKAN DAN PELATIHAN (DIKLAT) TERHADAP KINERJA KARYAWAN TETAP PADA UNIT AVIATION SECURITY DIVISI OPERATION & SERVICE PT. ANGKASA PURA II (PERSERO) CABANG BANDARA SULTAN SYARIF KASIM II PEKANBARU - Hendra, Teguh (Sekolah Tinggi Ilmu Ekonomi Riau, 2022)
Human resources are the driving force for all company activities. HR support must also be seen from the quantity and quality of human resources. Performance is basically what employees do so that it affects many contributions to the agency or organization, including the quality of services provided. In improving employee performance, it is necessary to develop appropriate human resources. One of the factors that can be used to improve employee performance include individual abilities (knowledge, skills and abilities), effort devoted, and organizational support. In general, the purpose of this study is to determine the effect of Education and Training (DIKLAT) on performance. The number of samples in this study were 80 employees. In the overall validity test of the statement items, the Education and Training variable (DIKLAT) and the Performance variable were declared valid because the value of rcount > rtable (0.2199). The results of simple linear regression obtained the value of Y = 13,506+ 0,666X. From the results of the partial test or t test, the value of tcount (6.905)> ttable (1.990) with a sig level of 0.000 <0.05 means that Education and Training (DIKLAT) has a significant effect on performance. The result of the coefficient of determination test (R2) is 0.379 or 37.9%. So it can be said that the variable Education and Training (DIKLAT) contributes to changes in the Performance variable by 37.9%. while the remaining 62.1% (100%-37.9%) is influenced by other factors not examined in this study